Procedings of the British Machine Vision Conference 2016 2016
DOI: 10.5244/c.30.86
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional aggregation of local evidence for large pose face alignment

Abstract: Methods for unconstrained face alignment must satisfy two requirements: they must not rely on accurate initialisation/face detection and they should perform equally well for the whole spectrum of facial poses. To the best of our knowledge, there are no methods meeting these requirements to satisfactory extent, and in this paper, we propose Convolutional Aggregation of Local Evidence (CALE), a Convolutional Neural Network (CNN) architecture particularly designed for addressing both of them. In particular, to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…Comprehensive results in Sec. 4 have shown that the more fusion we conducted to the baseline network, the better performance we can get. Input image fusion.…”
Section: Boundary-aware Landmarks Regressormentioning
confidence: 98%
“…Comprehensive results in Sec. 4 have shown that the more fusion we conducted to the baseline network, the better performance we can get. Input image fusion.…”
Section: Boundary-aware Landmarks Regressormentioning
confidence: 98%
“…Finally, it is worth mentioning the advent of facial landmark localisation using Deep Learning [5], [30], [52]. However, despite achieving impressive accuracy, these techniques are far from being able to operate at real-time speed.…”
Section: Prior Work On Face Trackingmentioning
confidence: 99%
“…A common approach to facial landmark detection problem is to learn a regression model [31,64,75,5,73,7,63]. Many of them leverage deep CNN to learn facial features and regressors in an end-to-end fashion [51,31,73] Another category of facial landmark detection methods takes the advantages of end-to-end training from deep CNN model to learn robust heatmap for facial landmark detection [27,57,6,4]. Wei et al [27] and Newell et al [34] take the location with the highest response on the heatmap as the coordinate of the corresponding landmarks.…”
Section: Facial Landmark Detectionmentioning
confidence: 99%